Synthesis and evaluation of anticancer activity of quillaic acid derivatives: A cell cycle arrest and apoptosis inducer through NF-κB and MAPK pathways - Huang, Xing; Zhang, Chang-Hao; Deng, Hao; Wu, Dan; Guo, Hong-Yan; Lee, Jung Joon; Chen, Fen-Er; Shen, Qing-Kun; Jin, Li-Li; Quan, Zhe-Shan (Frontiers in Chemistry, 2022)
A series of quillaic acid derivatives with different substituents on the 28-carboxyl group were designed and synthesized. Five human cancer cell lines (HCT116, BEL7402, HepG2, SW620, and MCF-7) were evaluated for their antitumor activity in vitro. Some of the tested derivatives showed improved antiproliferative activity compared to the lead compound, quillaic acid. Among them, compound E (IC50 = 2.46 ± 0.44 μM) showed the strongest antiproliferative activity against HCT116 cells; compared with quillaic acid (IC50 > 10 μM), its efficacy against HCT116 cancer cells was approximately 4-fold higher than that of quillaic acid. Compound E also induces cell cycle arrest and apoptosis by modulating NF-κB and MAPK pathways. Therefore, the development of compound E is certainly valuable for anti-tumor applications.